AB0598 Serum defensin level in systemic sclerosis patients. (15th June 2017) - Emiroglu, T; Küçük, H; Goker, B; Haznedaroglu, S; Pasaoglu, H; Varan, Ö; Öztürk, MA; Pasaoglu, OT; Tufan, A
Abstract : Background: Skleroderma is an autoimmune disease characterized by fibrosis of skin and lung as well as involvement of kidney, gastrointestinal system and heart (1). Etiology and exact mechanism of disease is poorly understood. A small number of studies have examined the role of AMPs on autoimmune diseases. It has been demonstrated that the amount of alfa- and beta-2 defensin serum levels are increased in systemic lupus erythematosus patients (2.3). Likewise, the association between AMPs and other diseases such as idiopathic pulmonary fibrosis, diffuse panbronchiolitis, pulmoner alveolar proteinosis and psoriasis has been reported (4). Objectives: No study investigated the role of AMPs on scleroderma patients. Hence, we aimed to investigate AMP serum levels and their possible association in these patients. Methods: There were 42 patients (40 female, mean age 42 years) and 38 healthy subjects (32 female, mean age 38 years) in the study. For SSc patients, the following data were recorded at enrollment: disease subset (limited/diffuse), autoantibodies (antinuclear, anti-centromere (ACA), and anti-scl), blood tests, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP), modified Rodnan skin score, presence and history of digital ulcers, presence and history of involvement kidney and gastrointestinal system, interstitial lung disease detected by chest HRCT and pulmonary function tests, estimated pulmonary arterial systolic pressure at echocardiography. Results: There were 42 patients (40 female, mean age 42 years) and 38 healthy subjects (32 female, mean age 38 years) in the study. Twenty-nine of the patients had diffuse systemic sclerosis and thirteen of the patients had limited systemic sclerosis. Average disease duration is 5.5 years. Pulmonary involvement was detected in twenty patients. The levels of beta 1 and beta 2 defensin that are epitelyal defensins were higher than control group but it has not reached statistical significance. (beta-1 defensin 235±178 vs 185±24 pg/ml, p=0.08 and beta2 defensin 253±453 vs 152±101 pg/ml, p=0, 1). Alpha defensin levels in scleroderma patients were significantly higher than control group (563±415 vs 377±269 ng/mL, p=0.02). In sub-group analysis patients with interstitial lung disease had a higher level of alpha defensive than those without involvement (684±473 vs430±299 ng/ml, p=0.04). There was an negative correlation between alfa defensin and Rodnan score (r=0.30) and CRP (r=0.34). Conclusions: Alpha defensin levels in scleroderma patients were significantly higher than control group, There may be an increase in the level of alpha defensin in a cause of vasulopathy in scleroderma patients References: Almeida, C., I. Almeida, and C. Vasconcelos, Quality of life in systemic sclerosis. Autoimmunity reviews, 2015. 14(12): p. 1087–1096. Vordenbäumen, S., et al., Elevated levels of human beta-defensin 2 and human neutrophil peptides in systemic lupus erythematosus. Lupus, 2010. 19(14): p. 1648–1653. Sthoeger, Z.M., et al., High α-defensin levels in patients with systemic lupus erythematosus. Immunology, 2009. 127(1): p. 116–122. Jansen, P.A., et al., β-Defensin-2 protein is a serum biomarker for disease activity in psoriasis and reaches biologically relevant concentrations in lesional skin. PloS one, 2009. 4(3): p. e4725. Disclosure of Interest: None declared